1996
DOI: 10.2169/internalmedicine.35.512
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia-Like Syndrome Induced by Overdosage of Cibenzoline.

Abstract: A case of cibenzoline-induced myasthenia-like syndrome is reported. A 67-year-old woman with renal failure and no previous disorder of neuromuscular junction complained of fatigue during climbing up a flight of stairs and experiencing heavy eyelids after administration of100 mg/ day of cibenzoline. Repetitive nerve stimulation tests revealed decrement at 5-10 Hz. After reduction of the dosage, myasthenia-like signs and symptomsdisappeared. The peak cibenzoline concentration was still high even after the dose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Ne g a t i v e T wa v e p e r s i s t e d u n t i l 4 7 t h d a y o n t h e E CG f i n d i n g s a n d t h e n g r a d u a l l y n o r ma l i z e d . (8,9 (3,5,6,11) and hypokalemia (12 …”
Section: F I G U R E 2 Ch E S T X R a Y F I L M A N D T We L V E -Lmentioning
confidence: 99%
“…Ne g a t i v e T wa v e p e r s i s t e d u n t i l 4 7 t h d a y o n t h e E CG f i n d i n g s a n d t h e n g r a d u a l l y n o r ma l i z e d . (8,9 (3,5,6,11) and hypokalemia (12 …”
Section: F I G U R E 2 Ch E S T X R a Y F I L M A N D T We L V E -Lmentioning
confidence: 99%
“…Recently, Kasuga et al 5 reported a case of mild myasthenialike syndrome induced by cibenzoline in a patient with renal failure. We suggest that particular caution is needed if cibenzoline is given to patients with renal dysfunction.…”
mentioning
confidence: 99%